How can we make it happen? From description to foresight of online learning environments - Tamborra, Valeria; Baldassarre, Michele (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
This paper proposes a Learning Analytics approach aimed at the study of event-driven data coming from 18 courses activated within a Moodle platform concerning two categories: post-graduate training courses and courses activated in the context of larger research projects. The objective is to identify possible patterns of interaction on the part of users enrolled in the two course categories in order to give useful indications for an effective Learning Design of future courses. The context of higher education, in particular the post-graduate one, is the field in which research on the field can find more fertile ground: training is often provided in e-learning mode, consistently with the need to make the training flexibly responding to the needs of an adult user, inserted in a context of lifelong learning.